Functional fitness norms and trends of community-dwelling older adults in urban China - Yanan Zhao (Nature Portfolio, 2021)
Abstract This study aimed to (1) establish age- and sex-specific functional fitness (FF) norms in Chinese older adults living in urban communities and (2) explore ageing-related degradations and sex differences in each FF dimension. A pool of 2398 individuals (1128 men; 1270 women) aged 60–98 years were recruited from urban communities of Nanjing, China. FF was measured using the Senior Fitness Test battery. FF norms were established for men and women in 5-year age intervals using five percentiles (10th, 25th, 50th, 75th, 90th). Significant degradations in FF were correlated with increases in age. Around half of test items in 75–79 years group (3 for men; 4 for women) and over half in 80–84 years group (5 for men; 4 for women) exhibited significant decreases in FF compared with the adjacent younger group, indicating that ages of 75 and 80 years are two potential turning points in FF declines. Significant differences existed between the overall FF of men and women; women outperformed men in flexibility and men outperformed women in upper body strength, agility/dynamic balance, and aerobic endurance. Significant age and sex effects occurred in each fitness dimension, which helps individualised program design and promotes an active lifestyle in older adults.